Understanding the Relationship between Depression and Chronic Diseases Such as Diabetes and Hypertension: A Grounded Theory Study - Pablo Alberto Herrera (MDPI AG, 2021)
There is a bi-directional relationship between depression and chronic illnesses such as diabetes and hypertension. This comorbidity is associated with higher mortality risk and diminishes the efficacy of interventions. The specific mechanisms of this mutual influence are still not fully understood, and most intervention protocols address these conditions separately. This study aims to improve our understanding of this relationship. We interviewed 18 patients and 24 health care professionals, focusing on understanding the different ways in which depression and chronic illness could influence each other. Our results show a common cyclical pattern and specific situations where the reported bi-directional relationship does not occur. We discuss the importance of opening a space for the patient’s grief process after the chronic illness diagnosis, managing the demands and stress of the patient’s treatment, and how to adjust the treatment to the different needs and possibilities of each person.